ANALISIS KAUSALITAS ANTARA KEBIJAKAN INVESTASI, DIVIDEN, DAN PENDANAAN PADA PERUSAHAAN MANUFAKTUR YANG LISTED DI BURSA EFEK JAKARTA - SE., MM.,, Muhammad Sulhan, (IQTISHODUNA, 2006)
This research try to analyze causality among investment, dividend, and financing on the listed manufacture companies at the Jakarta Stock Exchange, that can be used for making policies in the future. There are two contradictory opinions about the theory of investment, dividend, and financing policies between Modigliani Miller with Bhattacharya that is about asymmetry information which is showed by causality between investment, dividend, and financing policies. The contradictory opinion is very interesting to be analyzed further in this research.This research was conducted by taking samples of manufacture companiesÂ  listed at the Jakarta Stock Exchange. Sample we selected by purposive sampling, in the form of companies that have cash dividend for three years continuously. Manufacture company is chosen as the research object because manufacture company have fixed assets serving as dominant investment elements of the total company assets.Results of this research show the negative causality between investment with dividend policies. The other result of this research show the positive causality between investment with financing policies and the positive causality between dividend with financing policies. Implication of the results are company manager to be wiser in dividend payment, the increase of retained earning in financing patterns, and the addition of long term debt with limited borrowing capacity.